The relationship between fibroblast growth factor 21 with biochemical parameters, anthropometric measurements and dietary intake in type 2 diabetic patients - Mirzaee, Elham; Payahoo, Laleh; Ghoreishi, Zohreh; Razmi, Hamireza; Amirpour, Mehdi (Progress in Nutrition, 2023)
Background: Fibroblast growth factor-21 (FGF-21), as a novel cytokine, plays an important role in the improvement of glucose and lipid metabolism via different metabolic pathways. Therefore, the aim of this study to investigate the relationship between FGF-21 and metabolic profile parameters in patients with type 2 diabetes mellitus (T2DM) compared to healthy controls. Methods: In this cross-sectional study, 85 patients with T2DM and 79 healthy subjects were recruited. Anthropometric measurements, dietary intake and biochemical measurements were assessed for all participants. Results: Serum levels of FGF-21 were negatively associated with hip circumference (HC) (β= -0.267, p= 0.038) and dietary proteins (β = -0.273, p= 0.005) in healthy subjects. Moreover, dietary carbohydrate intake was inversely associated with FGF-21 (β= -0.183, p=0.041) in the total population. Also, serum levels of total cholesterol (TC), low density lipoprotein-cholesterol (LDL-C) and fasting blood sugar (FBS) in diabetic patients were significantly higher than those in healthy subjects (p<0.05); However surprisingly, triglyceride (TG) and fasting insulin levels were significantly higher in healthy subjects (p<0.05). Tumor necrosis factor-α (TNF- α) was positively associated with LDL-C in healthy subjects as well as FBS and hemoglobin A1c (HbA1c) in all participants. Serum TNF-α levels had a significant positive association with body mass index (BMI) (β= 0.303, p= 0.004) and HC (β= 0.294, p= 0.012) in patients with T2DM. Conclusions: Our findings revealed that dietary intake of protein and carbohydrates were inversely associated with serum levels of FGF-21. Therefore, more detailed studies are needed in order to reach a robust conclusion.